MR findings in acute and chronic coccidioidomycosis meningitis. - Wrobel, C J; Meyer, S; Johnson, R H; Hesselink, J R (American Journal of Neuroradiology, 1992)
PURPOSE To characterize MR findings in acute and chronic coccidioidomycosis meningitis and relate the imaging features to the clinical course.METHODS We reviewed MR scans and clinical findings of 12 patients with coccidioidal meningitis.RESULTS Patients with active or untreated disease were found to have hydrocephalus and intense enhancement of the cervical subarachnoid space, basilar, sylvian, and interhemispheric cisterns on postcontrast MR scans. Focal parenchymal signal abnormalities suggesting ischemia or infarction were common. Abnormal MR enhancement decreases during therapy, although patients develop cortical and/or brain stem atrophy.CONCLUSIONS Widespread cisternal and cervical subarachnoid meningeal involvement is common in coccidioidal meningitis. Serial contrast MR imaging reflects the effects of therapy in patients with coccidioidal meningitis.